Evaluation of a Live-Attenuated Human Parainfluenza Virus Type 2 Vaccine in Adults and Children. Issue 3 (3rd January 2023) - Karron, Ruth A; Herbert, Kristi; Wanionek, Kimberli; Schmidt, Alexander C; Schaap-Nutt, Anne; Collins, Peter L; Buchholz, Ursula J
Abstract: We conducted a phase I clinical trial of the live-attenuated recombinant human parainfluenza virus type 2 (HPIV2) vaccine candidate rHPIV2-15C/948L/∆1724 sequentially in adults, HPIV2-seropositive children, and HPIV2-seronegative children, the target population for vaccination. rHPIV2-15C/948L/∆1724 was appropriately restricted in replication in adults and HPIV2-seropositive children but was overattenuated for HPIV2-seronegative children.